2021
DOI: 10.1128/mra.00402-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Burkholderia gladioli Myophage Mana

Abstract: Burkholderia gladioli is known to cause respiratory tract infections in cystic fibrosis patients. Here, we describe the annotation of the 38,038-bp genome sequence of Mana, a P2-like phage of B. gladioli. Understanding the genomic characteristics of phages infecting pathogens like B. gladioli can lead to advancements in phage therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Regarding the genus Burkholderia, in 2021, Godoy et al [69] reported the genome sequence of a P2-like phage of Burkholderia gladioli, a ubiquitous Gram-negative with a recognized ability to infect pwCF. The phage was isolated from soil and sequenced to characterize its main features, in order to advance knowledge on alternative treatments for B. gladioli infections.…”
Section: B Cepacia Complexmentioning
confidence: 99%
“…Regarding the genus Burkholderia, in 2021, Godoy et al [69] reported the genome sequence of a P2-like phage of Burkholderia gladioli, a ubiquitous Gram-negative with a recognized ability to infect pwCF. The phage was isolated from soil and sequenced to characterize its main features, in order to advance knowledge on alternative treatments for B. gladioli infections.…”
Section: B Cepacia Complexmentioning
confidence: 99%